Requirements for large-scale adoption of rapid manufacturing technologies - Saad Hasan; Allan Rennie; Mohammad Rashedul Hoque; Md. Nisar Ahmed Shams (Cogent Business & Management, 2019)
Despite the use of Additive Manufacturing (AM) technologies in a lot of applications including the production of some high-value products for end use, it is still very much an untapped potential. There is an increase in usage of AM technology for the manufacture of end-use products (Rapid Manufacturing (RM)) in recent years, but mass use of the technology in terms of speed, cost and quality, which is acceptable by the general consumer, is still not widely in existence today. The concept of RM as a viable production process is still not understood by many businesses/consumers, with thinking still dominated by the AM technologies for Rapid Prototyping (RP) applications. A key difference between RM and RP is in the supply chain. The RM supply chain is much more complicated than the RP supply chain. This research conducted a Delphi Study to identify the requirements or pre-requisites necessary for the use of RM technologies as a viable means to manufacture end used products (RM application of AM) in mass scale. The paper identifies 36 requirements or pre-requisites and classified them into various classes of importance in order to highlight their significance. In addition to supply chain issues, the requirements unearthed are factors or features about RM technology (equipment), materials and processes that need modification, upgrading or creation.
Keywords: 650; Rapid manufacturing; additive manufacturing; rapid prototyping; supply chain; technology; Delphi study